Bermain sebagai Metode Pembelajaran bagi Anak Usia Dini (THUFULA, 2015)
Every parent can certainly always look forward to the baby’s presence.The presence of children would add to the happiness in the household. For getting good education, children should start it at their early age even while still in the womb. Early childhood between 4 to 6 years known as pre-school age children are by the experts called them as the golden age, because the intellect in this period increased by 50%. There are so many methods that can be done to children aged prematurely. One of them is playing. Learning while playing or playing while learning can be fun and entertaining for children. Playing will improve aspects of physical, mental, intellectual and spiritual children. They will find new things thathave not ever known before. The playing has benefits and influences for children, including strengthening the physical (body) through muscular movements, develop personality, improve communication, and so on. The types of play that can be done is through the method of social playing, playing with objects and as well as playing a role. Each of these methods has its advantages and disadvantages of each. However, the important thing is not to impose less favorable learning them, because basically the world is a world-age children play, playing while learning or learning through playing method.